Development of Visual-Spatial Thinking Ability Test Instrument Based on Pattern Batik Ceplok-Ceplok Jatipelem Jombang - Farabi, Muhammad Al; Masamah, Ulfa; Rofiki, Imam (Jurnal Riset Pendidikan dan Inovasi Pembelajaran Matematika, 2025)
Visual-spatial thinking ability is an important ability for students in understanding and solving geometry problems. This study aims to develop a test instrument for students' visual-spatial thinking ability based on pattern batik Ceplok-Ceplok Jatipelem Jombang. This research is a development research (R&D) with the Tessmer model which consists of preliminary, self evaluation, expert reviews, one-to-one evaluation, small group evaluation, and field test evaluation stages. The subjects of this study were students of class IX MTs Negeri 3 Jombang. The data collection techniques used were questionnaires, interviews, and walkthroughs through test instruments and validation sheets. Analysis of the test results was carried out with the Rasch model approach assisted by Ministep software. The results obtained 4 items of descriptive questions that fulfill (1) Validity is satisfied based on the 0.5 < MNSQ < 1.5, -2.0 < ZSTD < +2.0, dan 0.4 < Pt Measure Corr < 0.85; (2) Reliability of respondents is categorized as sufficient, items are categorized as excellent, and the relationship between the two is categorized as good; (3) The level of difficulty of the test instrument varies at the easy, medium, and difficult levels. (4) The differentiating power of the questions is categorized as good and very good to use. So, it shows that the test instrument to measure the ability of visual-spatial thinking based on pattern batik Ceplok-Ceplok Jatipelem Jombang on geometric transformation material satisfies the criteria worthy to be used.